Pembangunan Sistem Informasi Inventory Berbasis Web (Studi Kasus: CV. Penerbit Nilacakra) - Kadek Ambali Yasa; Ketut Queena Fredlina; I Gede Juliana Eka Putra (Primakara University, 2023)
Information system is a system that processes and provides information for decision making within an organization. Inventory information system is a system used to process and provide information about inventory data in a company for decision making. Inventory Information System In CV. Nilacakra publishers still use manual processes. The purpose of this study was to develop an ongoing inventory information system at CV. Nilacakra Publisher to support web-based control. The methodology used to develop this inventory information system is the waterfall method and uses the PHP and MySQL programming languages.